Protecting stateless persons : the implementation of the Convention Relating to the Status of Stateless Persons across EU states - Bianchini, Katia (International refugee law series, 2018)
In Protecting Stateless Persons: The Implementation of the Convention Relating to the Status of Stateless Persons across EU States, Katia Bianchini offers a study of legislation, case-law and decision-making concerning the protection of stateless persons in ten EU Member States. --